F = 9/5 C + 32
- 32 -32
subtracting - 32 from both sides
F - 32 = 9/5c
5/9 F -32 = 5/9(9/5)C
Invert 9/5 to 5/9 multiply to both sides
5/9F - 32 = C
The answer is 5/9F-32 = C
Answer:
![y = x-7](https://tex.z-dn.net/?f=y%20%3D%20x-7)
Step-by-step explanation:
<u>Step 1: Write the equation in point-slope form</u>
Point Slope Form: ![y-y_{1}=m\left(x-x_{1}\right)](https://tex.z-dn.net/?f=y-y_%7B1%7D%3Dm%5Cleft%28x-x_%7B1%7D%5Cright%29)
<u>Plug in the numbers and solve</u>
<u />![y - (-2) = 1(x - 5)](https://tex.z-dn.net/?f=y%20-%20%28-2%29%20%3D%201%28x%20-%205%29)
![y + 2 = x - 5](https://tex.z-dn.net/?f=y%20%2B%202%20%3D%20x%20-%205)
![y + 2 - 2 = x - 5 - 2](https://tex.z-dn.net/?f=y%20%2B%202%20-%202%20%3D%20x%20-%205%20-%202)
![y = x-7](https://tex.z-dn.net/?f=y%20%3D%20x-7)
Answer: ![y = x-7](https://tex.z-dn.net/?f=y%20%3D%20x-7)
Answer:
x > 10/7 or x > 1 3/7
Step-by-step explanation:
First simplify the left side of the inequality.
6x+ 1/4 (4x+8)> 12
6x+x+2>12
7x+2>12 Next, using the property of inequality, subtract two from both sides.
7x>10 Now divide by 7 to solve for x.
x>10/7 or x> 1 3/7
X(3y+2)-6(3y+2)
(x-6)(3y+2)
so the answer is 2+3y